LEGAL SUPPORT AND OPTIMISATION OF BULK CARGO TRANSPORTATION - Prodashchuk, Svitlana; Kim, Kateryna; Bohomazova, Hanna (SWorld-Ger Conference proceedings, 2025)
The paper examines the peculiarities of legal regulation of bulk cargo transportation in the national and international transport space, and outlines directions for optimising logistics processes using modern information technologies and safety standards.